Artemis Fowl. The Arctic incident : the graphic novel - Moreci, Michael (Disney Hyperion, 2021)
Artemis gets an urgent plea for help from a man he thought he would never see or hear from again--his father--and must join with the fairy police to save his father from the Russian Mafiya.